Did the Attitude of Banks Towards Corporate Social Responsibility Reporting Change Since the Last Global Financial Crisis? A Comparative Study of Conventional and Islamic Banks in the United Arab Emirates - Ben Douissa, Ismail; Azrak, Tawfik (International Journal of Economics and Financial Issues, 2017)
Scoring the disclosure of corporate social responsibility (CSR) practices of banks has been extensively studied in the literature. However, a few studies covered the voluntary aspect of CSR practices disclosure in the banking sector. While the responsibility of banks has been seriously targeted, this study tends to do a comparative analysis of the reaction of conventional and Islamic banks to the financial crisis regarding the disclosure of their CSR practices and the possible inclusion of CSR dimensions in their strategy. The sample consists of 18 listed Islamic and conventional banks operating in the UAE over the period 2006-2014. The findings indicate that conventional banks in the UAE integrated the CSR dimension in their strategy starting from 2009 in order to rebuild their images with their stakeholders. However, Islamic banks did not react to the global financial crisis and continued with the same reporting attitude as prior to the crisis. Keywords: Social responsibility, financial crises, banks. JEL Classifications: G01, G21, M14